Analysis of WhatsApp Media Usage Among Students of the Japanese Language Education Program at the University of Riau - Parma, Hani Killana; Sri Wahyu Widiati; Nana Rahayu (The Future of Education Journal, 2025)
This study aims to analyze the utilization of WhatsApp as a medium to support Japanese language learning among students of the Japanese Language Education Program at the Faculty of Teacher Training and Education, University of Riau. The research uses a descriptive quantitative approach, with data collection techniques through questionnaires and documentation of WhatsApp conversations in Japanese. A total of 38 students participated as respondents in this study. The results of the questionnaire indicate that the majority of students use WhatsApp for academic communication and informal Japanese language practice, although they still face challenges such as limited vocabulary and lack of self-confidence. Analysis of four screenshots of conversations shows that students are able to use Japanese contextually and coherently without relying on automatic translation, although the use of greetings remains limited. This study demonstrates that WhatsApp serves as a flexible learning medium that supports foreign language communication skills in an informal setting. The implications of these findings emphasize the importance of integrating digital media in foreign language learning to increase exposure and language practice outside formal classroom settings.